The U.S. Withdrawal from UNESCO under the Reagan Administration: A Multilevel Analysis - B. A. Avdeev (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The United States positions itself as a global leader and upholder of the world order whose pivotal role in the system of international relations is legitimized through its active participation in multilateral institutions. At the same time, it was the United States which resorted to unilateral actions more often than any other state, exerted significant diplomatic and financial leverage on international organizations to achieve its national interests, undermining the very principle of multilateral cooperation. This inconsistency has been most clearly manifested in the U.S. conflict behavior towards UNESCO — an integral part of the UN system, which focuses on addressing the global issues of the present. In terms of providing a better understanding of the logic behind the formation of the U.S. policy towards this organization and to the UN in general, the case of the first U.S. withdrawal from UNESCO in 1984 under the Reagan administration is of particular interest. On the basis of K. Waltz’s methodology of multilevel analysis the article reconstructs the chronology of the decision-making process, identifies its internal and external determinants, and outlines its key actors. The first section focuses on the systemic constraints that forced the Reagan administration to reconsider its attitude towards the UN system in general and UNESCO in particular. The second section examines the domestic political determinants of the withdrawal decision, centered around the results of complex bargaining between the key players in the American political system, government agencies and interest groups. The third section outlines the motivation and politicalpsychological portraits of individual politicians who were personally interested in pulling USA out of UNESCO. In this regard, the emphasis is given to the figure of the Assistant Secretary of State for International Organization Affairs G. Newell. In conclusion, the author argues that the withdrawal decision was deliberately made by ideologically motivated politicians in the Reagan administration, despite the alternative voices from Congress, a number of government agencies and civil society. It became a sort of response of the conservative-minded American establishment to changing international status quo, including the realignment of power in the UN specialized agencies.